(untitled) (Scientific journal of the Fergana State University, 2023)
In the article, it is emphasized that in the education system, the concept of eliminating the ecological danger in front of the society and transitioning to a sustainable path of development by eliminating the global, regional and local problems of ecological culture has been constantly changing in the human society for several thousand years.The main indicators of the scientific direction are the monitoring of changes in space and time, such as the use of nature and the amount of product production, the number of people, the scale of use of natural resources, the amount of anthropogenic pressure on nature, the balance of the ecological and ethno-ecological landscape necessity is analyzed.